Модульно-рейтинговая система оценки знаний обучаемых - Ганжа, В. А.; Чичко, О. И. (БНТУ, 2013)
One of the tools to improve the efficiency and quality of education is the implementation and use of the rating system, which firstly increases the impartiality of the evaluation of student's achievement in academics, secondly, the system more accurately assesses the quality of learning and, thirdly, it solves a psychological problem of stress.
The module-rating system for assessing students knowledge